Sulfur Dioxide Enhances Endogenous Hydrogen Sulfide Accumulation and Alleviates Oxidative Stress Induced by Aluminum Stress in Germinating Wheat Seeds. (11th May 2015) - Zhu, Dong-Bo; Hu, Kang-Di; Guo, Xi-Kai; Liu, Yong; Hu, Lan-Ying; Li, Yan-Hong; Wang, Song-Hua; Zhang, Hua
Abstract : Aluminum ions are especially toxic to plants in acidic soils. Here we present evidences that SO2 protects germinating wheat grains against aluminum stress. SO2 donor (NaHSO3 /Na2 SO3 ) pretreatment at 1.2 mM reduced the accumulation of superoxide anion, hydrogen peroxide, and malondialdehyde, enhanced the activities of guaiacol peroxidase, catalase, and ascorbate peroxidase, and decreased the activity of lipoxygenase in germinating wheat grains exposed to Al stress. We also observed higher accumulation of hydrogen sulfide (H2 S) in SO2 -pretreated grain, suggesting the tight relation between sulfite and sulfide. Wheat grains geminated in water for 36 h were pretreated with or without 1 mM SO2 donor for 12 h prior to exposure to Al stress for 48 h and the ameliorating effects of SO2 on wheat radicles were studied. SO2 donor pretreatment reduced the content of reactive oxygen species, protected membrane integrity, and reduced Al accumulation in wheat radicles. Gene expression analysis showed that SO2 donor pretreatment decreased the expression of Al-responsive genes TaWali1, TaWali2, TaWali3, TaWali5, TaWali6, and TaALMT1 in radicles exposed to Al stress. These results suggested that SO2 could increase endogenous H2 S accumulation and the antioxidant capability and decrease endogenous Al content in wheat grains to alleviate Al stress.